Effectiveness of the Traditional Game Patok Lele as a Dynamic Warm-Up Model to Enhance Students’ Physical Activity - Ade Ros Riza; Muhammad Fadli Boang Manalu; Ahmad Fauzi Lubis; Wan Aldi Fahmi; Enzi Yoel Fransiskus Tarigan; Diyah Salsabil Nasution; Mardongan Togatorop; Senia Mariana Sinaga; Kuntum Tamba G; Mutia Mutia (Joska: Jurnal Isori Kampar, 2026)
Purpose of the Study: This study aims to examine the effectiveness of the traditional game patok lele as a dynamic warm-up model for enhancing students’ physical activity levels. The game was evaluated as a culturally relevant strategy to stimulate physiological readiness before core Physical Education activities. Materials and Methods: This research employed a literature review method by analyzing relevant journals, books, and scientific sources related to traditional games, warm-up strategies, and physical activity in school settings. The reviewed literature focused on the physiological, pedagogical, and motivational impacts of integrating patok lele into Physical Education learning. Results: The analysis indicates that patok lele incorporates diverse movement patterns—including running, chasing, dodging, and rapid reactions—that effectively activate the cardiovascular system and prepare muscular function for subsequent learning activities. In addition to physiological benefits, the game increases student motivation and engagement due to its enjoyable and competitive nature. Literature findings show that the game promotes moderate-to-vigorous physical activity levels while also strengthening social skills such as cooperation and sportsmanship. Conclusions: Patok lele is an effective, educational, and culturally meaningful dynamic warm-up alternative for Physical Education. Its integration into school-based warm-up routines supports physical readiness, enhances student engagement, and fosters both physical and social development